The Sedimentary Process of Sand Deposits in Bogowonto River, Purworejo, Central Java, and Progo River, Kulonprogo, Yogyakarta Using Granulometric Analysis - Muchamad Ocky Bayu Nugroho; Yody Rizkianto; Riyan Ranggas Yuditama; Akbar Ryan; Agam Maulana (EKSPLORIUM, 2021)
ABSTRACT. Sedimentation is the most traditional separation technique and it is relying on efficient coagulation and flocculation to produce flocs with good settling properties. Bogowonto River and Progo River belong to South Serayu Area. There are similar geological processes that affected the river forming process i.e., erosional process, provenance, and fault systems. The sand sedimentation process for each river could be different due to geometry and river morphology. This research aims to reveal the possible parameters that affected the sedimentary process and sediment material along the stream river. Granulometric analysis was done in this research. Samples were taken from 3 points (upstream, middle, and downstream) of Bogowonto river and Progo river. Statistically, the upstream and middle stream of Bogowonto River shows more dunes and beach environment characters than Progo River. It could be interpreted if Bogowonto has more deposit plain like point bar than Progo River. The downstream area has been interpreted as the upper part of estuarine due to river and beach environment. The volcanic arc (Tertiary & Quarternary) is the main sediment source for these rivers. The sediment supply of the Progo River is strongly influenced by Merapi’s eruption whereas Bogowonto river is dominated by reworked Old Andesite Formation (OAF) & Sumbing’s material. Morphologically, Bogowonto has more meandering features than Progo that indicates the development of river stage in a long time and wide distributed sediment materials.ABSTRAK. Sedimentasi adalah teknik pemisahan yang paling tradisional dan tergantung pada koagulasi dan flokulasi yang efisien untuk menghasilkan flok dengan sifat pengendapan yang bagus. Sungai Bogowonto dan Sungai Progo termasuk dalam wilayah Serayu Selatan Selatan. Proses pembentukan sungai dipengaruhi oleh proses geologi seperti proses erosi, batuan asal, dan sistem sesar. Proses sedimentasi pasir yang terjadi pada kedua sungai tersebut dapat berbeda berdasarkan faktor geometri dan morfologi sungai. Penelitian ini bertujuan untuk mengetahui berbagai parameter yang mempengaruhi proses sedimentasi dan material sedimen di sepanjang aliran sungai. Metode yang digunakan adalah analisis granulometri pada sampel sedimen yang diperoleh dari 3 titik pada masing-masing sungai (hulu, tengah, dan hilir). Secara statistik, bagian hulu dan tengah Sungai Bogowonto memiliki karakter lingkungan pantai atau bukit pasir yang lebih banyak daripada Sungai Progo. Sungai Bogowonto diinterpretasikan memiliki lebih banyak dataran endapan seperti point bar dibandingkan Sungai Progo. Daerah hilir yang merupakan bagian atas dari muara menunjukkan karakter lingkungan sungai dan pantai yang dominan. Busur vulkanik (Tersier & Kuarter) merupakan sumber sedimen utama. Pasokan sedimen sungai Progo sangat dipengaruhi oleh erupsi Merapi sedangkan sungai Bogowonto didominasi hasil rombakan OAF & material Sumbing. Secara morfologi, Kali Bogowonto memiliki ciri lebih berkelok-kelok daripada Kali Progo yang menggambarkan tahap kedewasaan sungai dengan waktu yang lama dan penyebaran material sedimen yang luas.